DIAGNOSTIC MODELS OF 2-LEVEL FRACTIONAL FACTORIAL DESIGN OF IMMOBILIZED Candida rugosa LIPASE BIODIESEL PRODUCTION - ALI DEBA, ABDULKARIM; MOHAMMED, SULAIMAN; SA’IDU , HARUNA; MOHD ZAIN, NOR AZIMAH (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
This study examined the strength of the 2 level fractional factorial design in screening optimum biodiesel production parameters by examining the significant variables and variables interactions as displayed in the diagnostic models generated by the design expert software. The displayed experimental runs models (ANOVA and Diagnostic plots) and variables interaction of the models is and indication that all the biodiesel parameters investigated via 2-level fractional factorial design are fit and their significant factors were screened accordingly. This study supports the success of the previously published screening of significant factors of biodiesel production.